Analisis Perilaku Phubbing Berdasarkan Jenis Kelamin - Nurrissa Falsabillah; Fatma Nofriza (Departement of Mathematics Education, 2024)
This study was motivated by the phenomenon of many teenagers who have difficulty controlling their phubbing behavior around them. This phenomenon can be seen in social interactions, where someone ignores the person they are talking to by continuously focusing on their smartphone. This behavior also reflects a lack of mutual respect between individuals. Phubbing behavior describes individuals who are too focused on their smartphones. Many teenagers ignore interpersonal communication because they are busy with their smartphones, so this phenomenon is increasingly common among teenagers. This study aims to analyze differences in phubbing behavior based on the gender of students at SMPN 102 Jakarta. The research method used is descriptive quantitative, with data collection techniques using the Phubbing instrument developed by Karadag (2015) which has been modified and adapted. The scale used is the Likert scale. The research sample consisted of 36 students, consisting of 19 male students and 17 female students. The results of the statistical analysis showed no significant difference based on gender, but were included in the moderate category.